Os usos das tecnologias digitais de informação e comunicação em um curso na modalidade a distância: uma abordagem na teoria da atividade e na gênese instrumental - Dainese, Carlos Alberto (2013)
In the development of courses in Distance Education (DE), the uses of artifacts like Information and Communication Technology (ICT) predominate to create a virtual learning environment. However, these artifacts not always meet the expectations of the subjects, since, due to lack of experience, greater attention is paid to the functionalities of the artifact and the separation between users and computer systems; it is necessary to think about the technology in use. The aim of this study was to investigate the uses of ICT to develop a distance-learning training program in a public institution. This study was supported by the Activity Theory and Instrumental Genesis. The program offered three courses taught via Moodle Virtual Learning Environment, and the activities were developed through the use of ICT. The study included 1 teacher, 2 local tutors and 10 students geographically distant. The uses of ICT in the courses were described and analyzed according to: a) the program design and the teacher s interview, outlining the different stages of the program as an activity system, and b) through the records of Moodle, which allowed both the description of the Instrumental Genesis teacher, tutor and student, and the statistical analysis of changes through the frequencies of ICT. The results showed that changes in the courses and in the activity system of the program have a mutual relationship between the provision, by the teacher, of the types and frequencies of ICT, and the contradictions generated by the students and tutors uses. This study offers as contribution a genetic-historical approach of an activity system that allows for the reconstruction and analysis of the development through its internal contradictions. This can be used as a tool to model solutions in Distance Learning Education through the uses of ICT, allowing subjects to find their own solutions and expansion actions. Furthermore, this research emphasizes that, for the purposes of ICT in Distance Learning Education, it is necessary that the prescribed and intended procedures that the instructor is trying to implement be contrasted and adapted according to the processes that are being performed by other subjects